The Analysis of Services Quality and Satisfaction of BPJS Patient at X Public Health Center Counter Kediri City - Mohamad As’ad Efendy; Elon Bora Bili (Journal Of Nursing Practice, 2022)
Background: There are still many people who do not know about the National Health Insurance itself, the ease of treatment using the National Health Insurance has not been fully successful, because of the length of bureaucracy and the lack of facilities and infrastructure to support the National Health Insurance program. Purpose: The purpose of this study was to see correlation between services quality and satisfaction BPJS Patients. Methods: A correlational study methodology was used with a group of BPJS Patients. To obtain 30 individuals, a consecutive sampling procedure was used. The data was analyzed using the Spearman rho statistical test, with a significance threshold of = 0.05. Results: The data revealed that, of the 30 respondents, the majority, 26 respondents (80  percent), stated that the services quality was good, and the majority had adequate satisfaction, 25 respondents (83 percent ). The results of the analysis of the spearman rho test obtained a p-value = 0.000 which is less than the value of alpha (0.05) so it can be concluded that H0 is rejected, meaning that there is a relationship between the services quality and the satisfaction of BPJS patients at X Public Health Center Kediri City. Conclusion: Based on the study's findings, it is possible to conclude that there is a link between the services quality and the satisfaction of BPJS patients. The study's findings also suggest that services quality can increase satisfaction because patient will have loyalty if public health center can ensure services quality to BPJS patient.